Sensitivity of Antarctic freshwater algae to salt stress assessed by fast chlorophyll fluorescence transient. - Miguel Vilumbrales David; Skácelová Kateřina; Barták Miloš (Czech Polar Reports, 2013)
In this study, we investigated the effects of salt stress (2 mM NaCl) on excitation energy transfer from light harvesting complexes to photosystem II (PS II) in two Antarctic algal species: Klebsormidium sp. and Zygnema sp. Short-term salt stress led to a significant changes in the shape of chlorophyll fluorescence transient (OJIP). Analyses of the polyphasic fluorescence transients (OJIP) showed that the fluorescence yield at the phases J, I and P declined considerably with the time of exposition to salt stress. In both experimental species, OJIP transients reached lowest values of chlorophyll fluorescence signal after 30/60 min. of NaCl exposition. Then, OJIP shape and chlorophyll fluo- rescence showed species-specific recovery and rised towards original values (about 2/3 of untreated control). Analyses of chlorophyll fluorescence parameters derived from OJIPs showed that salt stress led to a decrease in the maximal efficiency of PS II photo- chemistry (FV/FM) in Zygnema sp. but not Klebsormidium sp. The results indicated that the probability of excitation energy transfer before and beyond QA, and the yield of electron transport beyond QA is limited by salt-induced stress in Zygnema sp. In addition, salt stress resulted in a decrease in the photosynthetic electron transport per PS II reaction center, but both increase and decrease in the trapping per PS II reaction center was found. Performace index (PIabs) was affected negatively in Zygnema sp. but possitively Klebsormidium sp. indicating that the latter species was more resistant to salt stress than Zygnema sp. Stres solí byl posuzován pomocí rychlé indukční kinetiky fluorescence chlorofylu OJIP. Bylo uskutečněno mezidruhové srovnání mezi řasami Zygnema sp. a Klebsormidium sp. In this study, we investigated the effects of salt stress (2 mM NaCl) on excitation energy transfer from light harvesting complexes to photosystem II (PS II) in two Antarctic algal species: Klebsormidium sp. and Zygnema sp. Short-term salt stress led to a significant changes in the ...